Association of angiotensin II type 1 receptor gene A1166C polymorphism with steroid sensitivity in children with nephrotic syndrome - Parvaneh Rahimi-Moghaddam; Seyyed Amir Yasin Ahmadi; Rozita Hoseini; Mehdi Chinichian; Parisadat Ahmadi (Society of Diabetic Nephropathy Prevention, 2019)
Introduction: In children, nephrotic syndrome is usually idiopathic. Cases are considered as minimal change disease until proven otherwise. The children who respond to steroid are called steroid sensitive, and the children who do not respond to steroid are called steroid resistant. Objectives: According to the role of genetic in effectiveness of steroid therapy of children with idiopathic nephrotic syndrome, we designed this study to investigate the role of angiotensin II type 1 receptor (AT1R) gene A1166C polymorphism in such conditions. Patients and Methods: This single center study was conducted on Iranian children in Hazarat Ali Asghar hospital, Tehran, Iran. A total of 40 patients (including 18 steroid resistant and 22 steroid sensitive patients) were selected. Total DNA samples were taken from peripheral blood. Polymerase chain reaction (PCR) was used for genotyping. Results: In this study, the association of AT1R gene A1166C polymorphism with groups including steroid sensitive and steroid resistant groups was not significant (P>0.05). We also found a significant difference of systolic blood pressure between steroid sensitive and steroid resistant group with more values in steroid resistant group (P=0.0327). Conclusion: This low power single center study could not show any significant association for this polymorphism in Iranian population. Resistance to steroid therapy was associated with higher systolic blood pressure.